CASSON FLUID FLOW WITH HEAT SINK AFFECTED BY SYMMETRIC WALL TEMPERATURE AND CONCENTRATION CONDITIONS - Hamza, M.M.; Bello, S.R.; Ibrahim, yazid; Bello, abdulkarim; Tasiu, Ahmad (Journal of Engineering and Technology (JET), 2024)
The problem of Casson fluid flow with heat sink impacted by symmetric wall temperature and concentration conditions has been investigated in this research. The leading equations of the formulated problem are solved analytically using the theory of simultaneous ordinary differential equations. The influence of several dimensionless factors relevant to the momentum, energy, mass diffusion, frictional force, heat transfer and mass transfer rates are investigated and depicted using illustrative graphs. It has been discovered that increasing the Casson fluid and heat sink values significantly reduces the fluid’s velocity and temperature. The existence of symmetric wall temperature and concentration substantially influences flow development and reversal. Casson fluids is commonly used in many notable technological and industrial properties, such as synthetic lubricants, specific oil paints, biological fluids, diverse polymer solutions to mention few. There are some features that defy comprehension when analyzed solely through lens of the Newtonian flow problem. Consequently, utilization of the non-Newtonian fluid motion is more productive.